Creation of facility for in-situ measurement of high-energy ionoluminescence on cyclotron DC-60 - Акилбеков, А; Скуратов, В; Даулетбекова, А; Гиниятова, Ш; Сейтбаев, А (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The complex of equipment for in-situ ion-luminescence (IL) measurements on the DC-60 cyclotron was created for the first time. The modes of measurement and interpretation of the ion luminescence spectra of LiF crystals as a benchmark system have been developed. “In-situ” studies of the structure and mechanical stresses have been performed on LiF crystals and radiation-resistant dielectrics which irradiated by fast heavy ions with high energy by ion-luminescence methods. The results on confocal and pulsed cathodoluminescence of LiF and Al 2 O 3 crystals are presented.